Impact of flooding events on buried infrastructures: a review - Abegaz, Ruth; Xu, Jun; Wang, Fei; Huang, Jie (Frontiers in Built Environment, 2024)
This review delves into the profound implications of flooding events on buried infrastructures, specifically pipelines, tunnels, and culverts. While these buried infrastructures are vital for community resilience, their susceptibility to damage from flooding, storm surges, and hurricanes poses significant challenges. Unlike the obvious impact on above-ground structures, the effects of flooding on buried infrastructures, being out of sight, are not quickly and easily observable. This review aims to (1) review the state-of-art research on the flooding effects on buried structures and summarize causes of failures of buried infrastructures induced by flooding; (2) identify the research gaps on this topic to motivate in-depth investigations; and (3) discuss the future research directions. This review shed light on how factors contributing to the vulnerability of buried infrastructure are multifaceted and can vary based on the specific characteristics of the infrastructure, the local environment, and the nature of the flood event. Despite the availability of many articles on the topic, this review also highlights a lack of methodologies to assess flooding damage and its impact on buried infrastructures. We suggested three future research directions to bridge this research gap including investigating and distinguishing key factors to quantify flooding damage to buried infrastructures, developing advanced modeling techniques, and exploring the integration of smart technologies in health monitoring of buried infrastructures.